Middle-aged Man with Deformities, Discomfort in the Chest, and Dextrocardia - Sriram Veeraraghavan, MD, DM; Bharath Raj Kidambi, MD, DM; Karthikeyan Balakrishnan, MD, DM (Journal of Clinical and Preventive Cardiology)
Congenital birth defects of brachy/polysyndactyly class can occur as isolated defects or as a part of syndromes and should raise suspicion of associated heart defects. Poland syndrome is one such congenital condition with its characteristic features. Although rare, it can significantly impact a patient’s quality of life due to its physical and psychological effects. This case report aims to contribute to the limited body of literature by detailing the clinical presentation, diagnosis, and cardiac defects associated with Poland’s syndrome.